P1-S5.36 Concurrency among women <25 years of age screened in family planning and reproductive health clinics in US Public Health Service Region X, January 2009–June 2010. (10th July 2011) - Nakatsukasa-Ono, W; Fine, D
Abstract : Background: To better understand the dynamics of STIs and HIV, researchers are increasingly examining the determinants and consequences of sexual networks. In January 2009, the Infertility Prevention Project (IPP) in US Public Health Service Region X-one of 10 regional projects funded by the Centers for Disease Control and Prevention (CDC)-began collecting a new network sexual risk behaviour for IPP chlamydia (CT) tests. The Region X IPP decided to collect sex partner (SP) concurrency based on the literature, research conducted in California, CDC input and regional interest. Methods: CT positivity (CT+) was calculated by demographics, sexual risk behaviours, SP concurrency and clinical findings for 94, 433 tests among women <25 years of age screened in Region X IPP family planning and reproductive health (FP/RH) clinics from January 2009 to June 2010. Univariate and multivariate analyses were conducted. Results: Of the 94 433 tests, 62% were age 20–24, and 72% were non-Hispanic white. 14% of clients reported their SPs definitely, 41% reported "possibly" and 38% reported it was "unlikely" their SPs had concurrent SPs in the last 12 months. CT+ ranged from 7.6% among clients reporting their SPs "definitely" had concurrent SPs to 5.2% among those reporting it was "unlikely." Clients reporting their SPs "definitely" or "possibly" had concurrent SPs were more likely to report other sexual risk behaviours and have clinical findings on examination. Significant (p<0.001) factors for CT+ included SP concurrency (definitely: AOR=1.20; possibly: AOR=1.25); age (15–19 years: AOR=1.34); race/ethnicity (Black: AOR=1.55; American Indian/Alaska Native: OR=1.60; Native Hawaiian/Other Pacific Islander: AOR=1.92); CT infection in the last 12 months (AOR=2.06); new SP (AOR=1.43), multiple SPs (AOR=1.48), symptomatic SP (AOR=4.07) in past 60 days; clinical findings (cervicitis or PID diagnoses; AOR=2.22). Conclusions: It is feasible to collect SP concurrency with female clients in the context of a clinic visit. SP concurrency was a significant predictor of CT+ beyond other risk factors. Results for clients who reported their SPs "possibly" had concurrent SPs may reflect clients being less knowledgeable about their SPs' sexual behaviours. Findings confirm the importance of assessing network characteristics such as SP concurrency, the need to incorporate SP concurrency in risk reduction counselling, and the potential to use this measure in empirically based screening decisions.